2014
DOI: 10.1155/2014/621342
|View full text |Cite|
|
Sign up to set email alerts
|

Practical Guidelines: Lung Transplantation in Patients with Cystic Fibrosis

Abstract: There are no European recommendations on issues specifically related to lung transplantation (LTX) in cystic fibrosis (CF). The main goal of this paper is to provide CF care team members with clinically relevant CF-specific information on all aspects of LTX, highlighting areas of consensus and controversy throughout Europe. Bilateral lung transplantation has been shown to be an important therapeutic option for end-stage CF pulmonary disease. Transplant function and patient survival after transplantation are be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 182 publications
(193 reference statements)
0
36
0
7
Order By: Relevance
“…2,14 Additionally, although an "ideal" lung donor has a smoking history of less than 20 years, 15 that benchmark often is not achieved, as evidenced by the 16.4% of donors listed in this study with a history of cigarette use. There are currently no studies that directly quantify how much past donor smoking is safe when accepting lungs for transplant; however, retrospective reviews have shown that more than 40 pack-years negatively influences outcomes in non-CF patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…2,14 Additionally, although an "ideal" lung donor has a smoking history of less than 20 years, 15 that benchmark often is not achieved, as evidenced by the 16.4% of donors listed in this study with a history of cigarette use. There are currently no studies that directly quantify how much past donor smoking is safe when accepting lungs for transplant; however, retrospective reviews have shown that more than 40 pack-years negatively influences outcomes in non-CF patients.…”
Section: Discussionmentioning
confidence: 90%
“…1 Lung transplant (LTx) is a therapeutic option for end-stage or acutely declining CF lung disease. 2 As such, CF is the second most frequent indication for bilateral LTx worldwide. 3 While LTx in CF is associated with improved median survival compared with other transplant indications, optimization of posttransplant outcomes and determination of risk factors for acute allograft rejection is ongoing in CF.…”
Section: Introductionmentioning
confidence: 99%
“…Использование прокинетиков и уменьшение объема питания поз-воляют избежать данных осложнений. Диета с высоким содержанием углеводов может стать причиной усиления продукции углекислого газа и усугубления дыхательной недостаточности, что является основанием для применения неинвазив-ной вентиляции легких [59].…”
Section: Review Articles and Lecturesunclassified
“…Подходы к поддержанию адекватного СП больных МВ непосредственно после ТЛ ввиду отсутствия достаточной базы данных основаны на стандартных рекомендациях для общей популя-ции пациентов хирургического профиля и боль-ных, перенесших трансплантацию других орга-нов [60]. Пероральная диета у пациентов, эксту-бированных на 1-е или 2-е сутки после операции, постепенно расширяется в зависимости от усво-ения больным продуктов питания с обязатель-ным применением заместительной ферментной терапии.…”
Section: Review Articles and Lecturesunclassified
“…The adult with CF should remain under the primary care of the transplantation team after a successful transplant and there should be shared care for pulmonary and non-pulmonary complications with the CF team. Primary care could be progressively handed over to CF teams with continued close liaison with the transplant centre [44].…”
Section: Lung Transplantationmentioning
confidence: 99%